Attraction Effects for Verbal Gender and Number Are Similar but Not Identical: Self-Paced Reading Evidence From Modern Standard Arabic - Tucker, Matthew A.; Idrissi, Ali; Almeida, Diogo (Frontiers in Psychology, 2021)
Previous work on the comprehension of agreement has shown that incorrectly inflected verbs do not trigger responses typically seen with fully ungrammatical verbs when the preceding sentential context furnishes a possibly matching distractor noun (i.e., agreement attraction). We report eight studies, three being direct replications, designed to assess the degree of similarity of these errors in the comprehension of subject--verb agreement along the dimensions of grammatical gender and number in Modern Standard Arabic. A meta--analysis of the results demonstrate the presence of agreement attraction effects in reading comprehension for gender and number on verbs. Moreover, the meta--analysis demonstrates that these two features do not behave identically: gender effects are larger and occur later relative to number attraction effects. These results challenge models of agreement that predict agreement features to be equipotent and show that real-time models of agreement require modifications in the form of cue-weighting in order to account for these differential results.